2007
DOI: 10.1189/jlb.1106695
|View full text |Cite
|
Sign up to set email alerts
|

Signaling through Gαi2 protein is required for recruitment of neutrophils for antibody-mediated elimination of larvalStrongyloides stercoralisin mice

Abstract: The heterotrimeric guanine nucleotide-binding protein Gαi2 is involved in regulation of immune responses against microbial and nonmicrobial stimuli. Gαi2 −/− mice have a selectively impaired IgM response consistent with a disorder in B cell development yet have augmented T cell effector function associated with increased production of IFN-γ and IL-4. The goal of the present study was to determine if a deficiency in the Gαi2 protein in mice would affect the protective immune response against Strongyloides sterc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Diffusion chambers containing larvae alone had small visible clots that stained positive for extracellular DNA indicating that ETs entered through the pores of the diffusion chamber. Chemotactic studies have demonstrated that a soluble extract of larval S. stercoralis directly recruits neutrophils in a CXCR2 [26] and Gαi2 [25] dependent manner. Neutrophils may have been attracted to soluble parasite material that diffused out of the diffusion chamber and in response underwent ETosis giving rise to ETs that entered the diffusion chamber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion chambers containing larvae alone had small visible clots that stained positive for extracellular DNA indicating that ETs entered through the pores of the diffusion chamber. Chemotactic studies have demonstrated that a soluble extract of larval S. stercoralis directly recruits neutrophils in a CXCR2 [26] and Gαi2 [25] dependent manner. Neutrophils may have been attracted to soluble parasite material that diffused out of the diffusion chamber and in response underwent ETosis giving rise to ETs that entered the diffusion chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils, eosinophils and macrophages are found in the parasite microenvironment in high numbers in naïve mice [24]. Neutrophils and eosinophils are directly recruited to the parasite microenvironment [2527], with neutrophils recruited in a CXCR2 [26] and Gαi2 [25] dependent manner. MPO from neutrophils is required for larval killing during innate and adaptive immune responses [24,28].…”
Section: Introductionmentioning
confidence: 99%
“…In mice, several components of protective primary and secondary immunity to the parasite have been described (17). Molecules from larval S. stercoralis directly recruit granulocytes to the parasite microenvironment (18)(19)(20), where they kill the parasite in collaboration with complement component C3 (21), eosinophil major basic protein, and neutrophil-derived myeloperoxidase (22,23). The cellular composition of the parasite microenvironment in naive mice consists of high numbers of neutrophils, eosinophils, and macrophages (22).…”
mentioning
confidence: 99%
“…If neutrophil recruitment in mice was blocked, because of a defect either in G␣i2 signaling (52) or in the expression of CXCR2 (21), the capacity of naïve and immunized mice to kill S. stercoralis larvae is significantly decreased. Adding neutrophils isolated from CXCR2 Ϫ/Ϫ mice directly into the larval microenvironment in recipient CXCR2 Ϫ/Ϫ mice restores larval killing (21).…”
mentioning
confidence: 99%